Applicability of Mönch's Fixed Point Theorem on Existence of a Solution to a System of Mixed Sequential Fractional Differential Equation. (28th May 2022) - Awadalla, Muath
Abstract : In this paper, we study the existence and uniqueness of the solution for a coupled system of mixed fractional differential equations. The main results are established with the aid of "Mönch's fixed point theorem." In addition, an applied example that supports the theoretical results reached through this study is included.